The Effect of Rapid Microwave Sintering Process on the Electrical Conductivity, Thermal Conductivity and Mechanical Properties of Al-TiC Composites - Yaghobizadeh,Omid (2018)
In this research, electrical conductivity, thermal conductivity and mechanical properties of the Al-TiC composites which were sintered via microwave-assisted process were investigated. The specimens were sintered for 3, 5 and 8 minutes. The results have shown that the sample which contains 4 vol. % TiC and was sintered for 8 minutes, has the highest electrical and thermal conductivities among the other obtained ones. Besides that, the sample which contains 8 vol. % TiC and was sintered for 3 minutes, has dedicated the highest hardness and density to itself. Scanning electron microscopy (SEM) micrographs have illustrated that by increasing the amount of TiC up to 12 vol. %, the agglomeration of particles occurs. The X-ray diffraction (XRD) investigations have shown that due to the short duration of the sintering process in the microwave method, there is no trace of TiO2 and Al4C3 as pernicious phases. According to the obtained results, it becomes clear that increasing the amount of TiC powder leads to the reduction of electrical and thermal properties of the samples and increasing the sintering duration, leads to the increase of the mentioned properties.